2017
DOI: 10.1002/anie.201701104
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Activity of Cobalt Porphyrin in CO2 Electroreduction upon Immobilization on Carbon Materials

Abstract: In ac omparative study of the electrocatalytic CO 2 reduction, cobalt meso-tetraphenylporphyrin(CoTPP) is used as am odel molecular catalyst under both homogeneous and heterogeneous conditions.Inthe former case,employing N,Ndimethylformamide as solvent, CoTPP performs poorly as an electrocatalyst giving low product selectivity in aslow reaction at ah igh overpotential. However,u pon straightforward immobilization of CoTPP onto carbon nanotubes,aremarkable enhancement of the electrocatalytic abilities is seen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
309
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(340 citation statements)
references
References 41 publications
11
309
0
Order By: Relevance
“…2019, 9,1900090 Figure 23. Conversely, Hu et al [75] proposed that [CoTPP] − formed after the Co's first reduction can directly form an adduct with CO 2 , while in homogenous form, this CO 2 adduct is primarily formed with [CoTPP] 2− , which requires higher overpotential (for the 2 electron reduction of CoTPP). Adapted with permission.…”
Section: Cobalt-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…2019, 9,1900090 Figure 23. Conversely, Hu et al [75] proposed that [CoTPP] − formed after the Co's first reduction can directly form an adduct with CO 2 , while in homogenous form, this CO 2 adduct is primarily formed with [CoTPP] 2− , which requires higher overpotential (for the 2 electron reduction of CoTPP). Adapted with permission.…”
Section: Cobalt-based Catalystsmentioning
confidence: 99%
“…[77] As previously reported, [75] solution-phase hybridization of cobalt phthalocyanine and MWCNT (in addition to carbon black and graphene) was adopted to modify the electrodes. [77] As previously reported, [75] solution-phase hybridization of cobalt phthalocyanine and MWCNT (in addition to carbon black and graphene) was adopted to modify the electrodes.…”
Section: Cobalt-based Catalystsmentioning
confidence: 99%
“…[18] In conclusion, [Co(qpy)] 2+ ,w hen combined to ac onductive material, like for example multi-walled carbon nanotubes,isahighly efficient supported homogeneous catalyst for the conversion of CO 2 to CO in water at neutral pH and with very low overpotential. [15] 0.25 550 3.2 0.08 91 CoPc-CN [16] 0.4 520 ca. Thea bility of the catalyst to be reduced with 2e lectrons and then to bind CO 2 at weakly negative potentials is ak ey to its exceptional selectivity.T he hybrid catalytic material is also stable over long period of time and current densities from 1mAcm À2 to ca.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[8] Another recent example is given by atetraphenyl Fe porphyrin with trimethyl ammonio groups appended at the para position of the four phenyl groups. Among several examples,F e [12] and Co [13][14][15] porphyrins as well as Co phthalocyanines [16,17] have been investigated. Formate production has been even more rare,w ith as example small iron clusters,s uch as [Fe 4 N(CO) 12 ] À reaching selectivity and Faradaic efficiency (FE) above 95 %, while the applied overpotential for the reaction is only 230-440 mV (pH 7-13).…”
mentioning
confidence: 99%
“…Without nitrogen, metal atoms can be embedded in the graphene either, also performing as a single-atom doped catalyst. [165,166] The overpotential could be decreased to −0.48 V. DFT investigations were performed to explain the superior activity of metal-porphyrin motif. Based on similar systems, He et al reported that Ag-and Cu-doped graphene was a potential electrocatalyst for CO2RR to methane and methanol respectively.…”
Section: Carbon-based Materialsmentioning
confidence: 99%